The Mediating Role of Process Stability in the Relationship Between Supply Performance and Product Quality Consistency Among SMES in Japing - Rendi Ferdiansyah; Bisma Jatmika Tisnasasmita; Yuli Kartika Dewi (Journal of Economics and Business UBS, 2026)
Product quality inconsistency is still a major challenge for food MSMEs due to high dependence on raw material supply and semi-manual production processes. This study aims to analyze the mediating role of process stability in the relationship between supply performance and product quality consistency in JAPA MSMEs. The research uses a quantitative approach supported by production operational data. Initial research used 120 production batches; after data screening for outliers, 90 observations were used in the final analysis. Data were analyzed using linear regression, path analysis, and Sobel tests. The results show that supply performance has a significant effect on process stability, but the direction of the influence is negative, so H1 is not supported. Process stability has a positive effect on product quality consistency, while supply performance does not directly affect product quality consistency. The Sobel test shows that process stability mediates the relationship between supply performance and product quality consistency. These findings confirm that improving the quality of food MSME products cannot be achieved solely through improving supply but requires strengthening the stability of the production process.